Amoebicidal Effect of COVID Box Molecules against Acanthamoeba: A Study of Cell Death - Ines Sifaoui; Rubén L. Rodríguez-Expósito; María Reyes-Batlle; Robert Sutak; José E. Piñero; Jacob Lorenzo-Morales (MDPI AG, 2024)
Acanthamoeba spp. can cause a sight threatening disease. At present, the current treatments used to treat Acanthamoeba spp. Infections, such as biguanide-based antimicrobials, remain inefficacious, with the appearance of resistant forms and high cytotoxicity to host cells. In this study, an initial screening was conducted against Acanthamoeba castellanii Neff and murine macrophages J774A.1 using alamarBlue™. Among the 160 compounds included in the cited box, 90% exhibited an inhibition of the parasite above 80%, while only 18.75% of the compounds inhibited the parasite with a lethality towards murine macrophage lower than 20%. Based on the amoebicidal activity, the cytotoxicity assay, and availability, Terconazole was chosen for the elucidation of the action mode in two clinical strains, Acanthamoeba culbertsoni and Acanthamoeba castellanii L10. A fluorescence image-based system and proteomic techniques were used to investigate the effect of the present azole on the cytoskeleton network and various programmed cell death features, including chromatin condensation and mitochondria dysfunction. Taking all the results together, we can suggest that Terconazole can induce programmed cell death (PCD) via the inhibition of sterol biosynthesis inhibition.